AB0079 Transdermal delivery of methotrexate in rheumatoid arthritis: are we deep enough?. (15th June 2017) - Sadarani, B; Majumdar, A; Kamble, P; Paradkar, S; Mathur, A; Sachdev, S; Chaudhari, P; Mohanty, B
Abstract : Background: Methotrexate (MTX), at low doses, is the first choice in the management of rheumatoid arthritis (RA). Despite its effectiveness, the probability of its discontinuation remains high due to adverse effects such as gastrointestinal intolerance, bone marrow toxicity as well as hepatotoxicity with conventional oral and parenteral therapy. 1 Transdermal delivery epitomizes an attractive alternative for drugs with systemic toxicities. The physicochemical characteristics of MTX such as high polarity and ionisation at physiologic pH make the development of its topical route of delivery challenging. 2 A new class of liposomes termed deformable or flexible liposomes have been reported to possess the virtue of stress-dependent adaptability that enables them to squeeze through interstices of stratum corneum and increase the depth of skin penetration. 3 Objectives: This study is intended to explore the transdermal route for the delivery of MTX in ameliorating its systemic toxicity without compromising the therapeutic effect in RA. Methods: MTX entrapped in deformable liposomes were prepared and characterised for particle size (PS) and entrapment efficiency (EE). They were incorporated into a hydroxyethyl cellulose gel base and evaluated for ex vivo skin permeation. Optimized liposomal gel was applied on the back of rats (3x4 cm area) and evaluated for its acute dermal toxicity and pharmacokinetics. Biodistribution was studied by topical application of 125 I labelled MTX incorporated liposomal gel in rats. Furthermore the efficacy of optimized gel was determined in collagen induced arthritis (CIA) in rats. Results: The optimized deformable liposomes exhibited a small PS of 110±20 nm and EE 35–50% while the liposomal gel showed a transdermal flux of 17.37±1.5 μg/cm 2 /hr in ex vivo skin permeation study. Topical application of liposomal gel depicted no clinical abnormalities or pathological changes at the site of application in rats. Pharmacokinetic data indicated sustained systemic delivery of MTX from its liposomal gel up to 48 hours. The gel resulted in lower accumulation of MTX in liver, kidneys and gut in contrast to intravenous administration of plain 125 I labelled MTX solution. In the CIA model, topical MTX gel administration demonstrated significant reduction in hind paw swelling and arthritic score, also validated by histological and radiographic examination of ankle joints and lowering of serum levels of cytokines like TNF-α and IL-6 in comparison to disease control group. Conclusions: The liposomal gel displayed dermal safety, sustained systemic delivery of MTX and its lower distribution to the organs of toxicity which may enable alleviating systemic side effects. Moreover, liposomal gel of MTX showed appreciable therapeutic efficacy in the CIA model. References: Braun J, Rau R. An update on methotrexate. Curr Opin Rheumatol. 2009;21(3):216–23. Prausnitz MR, Langer R. Transdermal drug delivery. Nat. Biotechnol. 2008;26(11):1261–68. Benson HA. Transfersomes for Transdermal Drug Delivery. Expert. Opin. Drug Deliv. 2006;3(6):727–37. Acknowledgements: DAE-BRNS Research Grant (sanction no. 2012/35/17/BRNS). Lipoids, Germany for gift sample of Phospholipon 90G, Gattefosse for gift sample of Labrasol and Signet for gift sample of Hydroxyethyl cellulose. Disclosure of Interest: None declared